Unilateral occipital condylar fracture presenting as neck pain and restriction of neck movements-Report of a case and review of literature - Manoj K Tewari; KL Ratnam; Vinod K Shiv (The Indian Journal of Neurotrauma, 2008)
Occipital condylar fractures (OCFs) once rare injuries are not so at present. A young male, victim of motor vehicle accident, presented with severe high cervical pain and restriction of neck movements without any focal neurological deficit, with normal cervical spine x-rays and computerized tomography (CT) scans brain. CT scan and magnetic resonance (MR) imaging of the craniovertebral junction (CVJ) area revealed a retro-pulsed segment in the cervical spinal canal with no cord compression or ligament injury. Patient improved with immobilization of neck. Patients with severe high cervical pain and restricted head movements OCF should be suspected and patient should be evaluated further. Majority of stable OCF improve with immobilization only.